EVALUASI PROGRAM PENGEMBANGAN KOTA HIJAU (GREEN CITY) DI KOTA KENDARI - Sri Mindasari; Hj Rostin (Universitas Halu Oleo, 2015)
This study aims to look at the planning of domestic waste water, solid waste, and green open spaces and green city program development (green city) in Kendari. Thedata used in this research is secondary data, obtained from the Department of City Planning and Department of Sanitation Kendari. Data processing method that analyzes the data. Analysis of the data used is descriptive analysis by using respondents. The scope of this research include an understanding of domestic waste water, waste, and green open spaces in the city of Kendari. Methods of data collection that is using the sample population. The results showed that the percentage generated for the planningof domestic waste water and solid waste reachedÂ 7.78% and 4.39% of the total percentage of collected while the green open spaces only reach 5.96% of the total percentage of the generated, this means planning green open spaces better than planning on wastewater domestic and waste carried by the municipal government of Kendari. Results of the research by using the sample population showed kendari city government is not quite ready to go green city (green city) from the aspect of domestic waste water and solid waste.